Chinese literature - Yao, Dan, 1968- (New York ; Cambridge)
[2], 251, [1] s.
Keywords: "Chinese literature has a long, distinctive history and has played an important part in shaping the cultural identity of the Chinese people. This literature provides a window into human relationships, society, politics, spirituality and philosophy at any given time in China's history. This accessible, illustrated introduction takes the reader through the rich Chinese literary tradition from ancient times to the twentieth century, exploring poetry, opera, drama, novels, short stories, the modern media and the authors who created these cultural treasures." --